¿No second chances? Criminal records as a legal-criminal issue - Villalobos Vallejos, Hugo (Revista de Estudios de la Justicia, 2018)
Criminal records are both normative and institutional consequences of criminal blame, given the legal registration of all criminal convictions. The current article analyze the legal nature of criminal record by recognizing an expressive function of punishment as a conventional device to express resentment and reprobation when criminal law is breached: If punishment is an expression of condemnation, then criminal records register this condemnation. The implications of the connection between punishment and criminal records allow us to conclude that any impact on fundamental rights of the ex-convicted through the preservation of criminal records is neither appropriate, necessary nor proportionate when the individual has fully served his sentence.